The human nucleoporin Tpr protects cells from RNA-mediated replication stress - Martin Kosar (Nature Portfolio, 2021)
Tpr nucleoporin is known to be essential for nuclear transport and mitosis processes. Here the authors explore the link between Tpr and genome instability providing insights into the role of Tpr in safeguarding cells from RNA-mediated replication stress.